Retail in a new world recovering from the pandemic that changed the world - Pantano, Eleonora (Emerald Publishing Limited, 2022)
The Covid-19 pandemic has dramatically changed retailing, creating an uncertain scenario that has forced marketers, retailers, and policy makers to face new challenges to survive and thrive. These challenges affect all aspects of retailing, from supply chain management to consumers' shopping experience, and from buying decisions to improving health and safety management for all stakeholders. A lot has been to do about the negative consequences of the pandemic on sales, mainly for traditional bricks-and-mortar retailers and small-scale independent shops. However, quite some retailers have demonstrated a remarkable agility in developing and applying new tools, frameworks, and approaches to secure their longevity, while also safeguarding employees' and consumers' safety. Retail In A New World: Recovering From The Pandemic That Changed The World provides an overview and assessment of the issues and opportunities for retailers that emerged during the Covid-19 pandemic. The book encourages readers to adopt future-facing, fresh approaches to retail management. The basis for guiding readers in this endeavour consists of a thorough synthesises of emerging studies on the dramatic consequences of Covid-19 pandemic, in an accessible way. Seeking to understand how retailers can adapt their strategies, this book presents empirical and theoretical contributions with case studies that illustrate innovative and provocative solutions. Retail In A New World proposes tools and frameworks that serve as basis to survive the pandemic and thrive in a post-pandemic scenario. New practices are introduced to ensure a safer shopping experience, including reducing consumers' anxiety about in-person purchases, more efficient management of crowds in the stores, and adopting new technologies and service scripts to support the change.